Impact of Occupational Stress of Employees on Company’s Performance in the Punjab and Gujarat Textile Sector of India - Kumar Sharma, Rakesh (Global journal of Business and Integral Security, 2024)
With the increasing demands of job requirements, organizational stress has become a prevalent issue in workplace. Work-related stress poses a significant challenge for organizations as it diminishes productivity, increases absenteeism, and contributes to various employee issues such as alcoholism, drug abuse, high blood pressure, and heart diseases. Occupational Stressors and the changing work environment over the past 40 years, economic globalization policies, which have influenced labour markets and work organisation, have increased work stressors. Other contributors to increasing job stress have included use of new information technologies that reduce the number of workers needed to produce goods or services, thereby increasing job insecurity, as well as declines in both union membership and labour production. Employers in manufacturing, healthcare, social services, and government are implementing new systems of work organisation, known as lean production, lean sigma, total quality management, or new public management and all of which are modern versions of scientific management or Taylorism, which can increase occupational stress. Occupational stress impacts not only occupation itself and organizational efficiency and effectiveness but it (Occupational Stress) has strong bearings on physiological, behavioural, and psychological aspects of employees. Indian Textile sector which is the second largest employment generator after agriculture and 7% of total Indian GDP needed special focus and attentions. Ultimate success or failure of an organization is determined majorly by the performance of their employees. Work stress really costs the companies and finally country’s economy billions of dollars. Textiles sector of India has partially been touched upon by the researchers with respect to occupational stress and its implications on performance. Present study highlights the specific areas of occupational stress and help the organizations to take remedial measures thru state-of-the-art diagnostic analysis. 12 insights pertaining to diversified areas e.g. role overload to unprofitability makes this research specific and unique. Prevailing stress level of employees is the independent variable whereas organization’s performance is the dependent variable. Effective and efficient stress management is the ultimate outcome of this study. Researchers, industry managers, employees, promoters, doctors, employee’s families, and government shall be the beneficiaries of this study.